A new promising way for tacklingthe 'Pharma Dilemma': artificialintelligence for clinical trials. (18th October 2019) - Harrer, Stefan; Antony, Bhavna; Bayat, Akram; Hu, Jianying
Abstract : Artificial intelligence (AI) is certainly not a panacea for solving the 'Pharma Dilemma', in which the cost of producing new drugs continues to spiral. However, AI can be used to fundamentally change the way we perform essential steps in clinical trial design and execution, from cohort selection to patient monitoring. Merging AI and clinical expertise across engineering and medical disciplines to explore the impact of these changes on trial performance and success rates is one of the most promising leads we have for restoring efficiency and sustainability to the drug development cycle.